A COMPARATIVE STUDY OF ANTI-ANGIOGENIC ACTIVITIES OF MEDICINAL PLANTS AND ITS THERAPEUTIC POTENTIAL IN ANGIOGENESIS-DEPENDENT DISORDERS - I, GLORY JOSEPHINE; Sd, Inbaraj; K, Kumaragurubaran; K, Punnagai; Ns, Muthiah (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Introduction Angiogenesis, the process of new vessel growth from pre-existing capillaries is involved in physiological and pathological process such as embryonic development, wound healing, diabetic retinopathy ,chronic inflammation, tumor growth and metastasis. Vascular endothelial growth factor (VEGF) induced angiogenesis plays an important role in the pathogenesis of diabetic retinopathy and cancer and anti VEGF factor agents are found to be effective . VEGF inhibitors from plant sources show promising result recently. So this study is designed to evaluate and compare the VEGF inhibitory effect of the herbs Osimum Sanctum, Andrographis paniculata, Syzygium cumini and Ginkgo biloba by using in vivo models. Methods: Both Corneal neovascularization assay and Chick Chorioallantoic membrane assays were used for evaluation. The induced neovascularization was compared with control and extract treated groups. Results: The acute and repeated dose toxicity tests showed that the extracts are safe on oral administration. And also the results showed significant antiangiogenic effect of individual extract and their combination in both in vivo models. However the combination of the extract showed excellent result (p <0.001) by reducing neovascularization in both models Conclusion: The above results suggested that combination of the above extracts have promising future in the management of angiogenesis dependent disorders. Key words: Osimum Sanctum, Andrographis paniculata, Syzygium cumini, Ginkgo biloba,Â Â Angiogenesis, chorioallantoic membrane, angiogenesis dependent disorders.